2021
DOI: 10.5603/fm.a2020.0091
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal mucosal cells in piglets fed with probiotic and zinc: a qualitative and quantitative microanatomical study

Abstract: Background: Probiotics and zinc are commonly used and beneficial in pig production. This work aimed to assess the effects of probiotic and zinc on the mucosal cells of the small intestine in respect to digestive capacity and immunity in pre and post-weaned piglets. Materials and methods: Eighteen LWY piglets were divided equally into control and treatment groups. The piglets were maintained in standard management conditions and were weaned at 28 days of age. The treatment group of piglets fed a mixture of prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For example piglets orally receiving a mix of a probiotic (1.25 × 10 9 CFU/day) and zinc (2000 ppm/day) showed the presence of stem cells at crypt base and elongation of the enterocyte microvilli in the small intestine, which can suggest an increased capacity to absorb nutrients and efficient resistance (Kalita et al, 2021). On the other hand, weaned pigs administered 2500 ppm of zinc oxide and/or a commercial mix of benzoic acid and probiotics (Bacillus licheniformis, Bacillus subtilis and Enterococcus faecium) showed that zinc oxide administrated alone had a stronger influence on the composition of the microbiota, although the microbiota of the ceacum in both groups of piglets was dominated by Firmicutes, followed by Bacteroidetes bacteria (da Silva et al, 2021).…”
Section: Probioticsmentioning
confidence: 99%
“…For example piglets orally receiving a mix of a probiotic (1.25 × 10 9 CFU/day) and zinc (2000 ppm/day) showed the presence of stem cells at crypt base and elongation of the enterocyte microvilli in the small intestine, which can suggest an increased capacity to absorb nutrients and efficient resistance (Kalita et al, 2021). On the other hand, weaned pigs administered 2500 ppm of zinc oxide and/or a commercial mix of benzoic acid and probiotics (Bacillus licheniformis, Bacillus subtilis and Enterococcus faecium) showed that zinc oxide administrated alone had a stronger influence on the composition of the microbiota, although the microbiota of the ceacum in both groups of piglets was dominated by Firmicutes, followed by Bacteroidetes bacteria (da Silva et al, 2021).…”
Section: Probioticsmentioning
confidence: 99%
“…IEL distributions also vary by locality within crypts and villi and in relation to luminal proximity, including location in the basement membrane, enterocyte nuclear level, or apical epithelium ( Figure 1 ). In porcine small intestine, IELs preferentially congregate to intestinal villi over crypts at up to a four-to-one ratio ( 65 67 , 77 , 78 , 83 , 97 , 98 ). Preferential accumulation of IELs in villi suggests IEL effector functions may involve close interactions with signals derived from the intestinal lumen, as villi are more intimately associated with the lumen compared to shielded niches of crypts.…”
Section: Introductionmentioning
confidence: 99%
“…IELs in small intestinal villi also differ in distribution across the epithelial layer in relation to luminal proximity. While the majority of IELs are located near the basement membrane, some IELs are in closer proximity to the lumen, including at the enterocyte nuclear level, apically, or even freely within the lumen ( 65 , 67 , 78 , 79 , 87 , 97 , 101 ). However, IEL detection within the free lumen must be cautiously interpreted, as technical variables of tissue processing may compromise tissue integrity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, zinc supplementation has been responsible for maintaining nonspecific defense mechanisms [8]. Kalita et al [9] already described the probiotic and zinc effects on the small intestinal mucosal cells in piglets.…”
Section: Introductionmentioning
confidence: 99%